2004
DOI: 10.1074/jbc.m409360200
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Membrane Trafficking Is Modulated by Multiple Interactions

Abstract: MUC1 is a mucin-like transmembrane protein found on the apical surface of many epithelia. Because aberrant intracellular localization of MUC1 in tumor cells correlates with an aggressive tumor and a poor prognosis for the patient, experiments were designed to characterize the features that modulate MUC1 membrane trafficking. By following [35 S]Met/Cys-labeled MUC1 in glycosylation-defective Chinese hamster ovary cells, we found previously that truncation of O-glycans on MUC1 inhibited its surface expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 68 publications
4
49
0
Order By: Relevance
“…Because Pseudomonas aeruginosa requires efficient internalization and activation along a multistep pathway for cell killing, the intracellular routing of the receptor/toxin complex rather than the binding to the target receptor on the cell surface may be rate limiting (28). The underglycosylation in MUC1 alters its internalization and subcellular localization due to truncated O-glycans (13). As toxin requires internalization for its cytotoxic effects, the membrane trafficking rate of the underglycosylated MUC1 in cancer cells would limit the efficacy of the immunotoxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Pseudomonas aeruginosa requires efficient internalization and activation along a multistep pathway for cell killing, the intracellular routing of the receptor/toxin complex rather than the binding to the target receptor on the cell surface may be rate limiting (28). The underglycosylation in MUC1 alters its internalization and subcellular localization due to truncated O-glycans (13). As toxin requires internalization for its cytotoxic effects, the membrane trafficking rate of the underglycosylated MUC1 in cancer cells would limit the efficacy of the immunotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this immunogenic peptide sequence is well suited as a target for cancer immunotherapy (9 -11). In addition, aberrant glycosylation of MUC1 also plays an important role in enhancing the internalization of MUC1 into the cytoplasm (12,13), making MUC1 a very attractive therapeutic target for immunotherapeutic reagents, including those that require delivery.…”
Section: Introductionmentioning
confidence: 99%
“…During this process a follow-up sialylation of glycan chains occurs [8]. In epithelial cells, the endocytosis and vesicular transport of MUC1 follows a dynamin-independent, clathrin-mediated pathway [9] requiring two specific tyrosine motifs in the highly conserved cytosolic MUC1 domain (Tyr20, Tyr60) as binding sites for the adaptor protein complex 2 and Grb2, respectively [10], whereas the re-entry of endocytosed MUC1 into the secretory pathway (recycling) was dependent on S-palmitoylation near the transmembrane domain [11]. In cancer cells, we found that MUC1 is contained in plasma membranous lipid rafts as platforms (B) Lipid rafts (dark blue bars) represent nanoscale assemblies of proteins that organize these proteins into platforms for targeted traffic within cells.…”
Section: The Cancer Mucin Muc1 Recycles Via Alternative Raft-associatmentioning
confidence: 99%
“…With transformation of normal epithelia to carcinomas, MUC1 is aberrantly overexpressed in the cytosol and over the entire cell membrane (Kufe et al, 1984;Perey et al, 1992). Cell membrane-associated MUC1 is targeted to endosomes by clathrin-mediated endocytosis (Kinlough et al, 2004). In addition, MUC1-C, but not MUC1-N, is targeted to the nucleus (Huang et al, 2003;Li et al, 2003a, b, c;Wen et al, 2003;Baldus et al, 2004;Wei et al, 2005) and mitochondria (Ren et al, 2004).…”
Section: Introductionmentioning
confidence: 99%